Environmental education as a tool for awareness and evaluation of proper solid waste management. - Aderaldo , Francisco Ícaro Carvalho; Lima , Tiago de Abreu; Aderaldo , Pedro Ítalo Carvalho; Gondim , Franklin Aragão (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The proper management of solid waste remains a challenge that requires attention not only from specific sectors but from society as a whole. Environmental education, as a crucial mechanism for disseminating knowledge about environmental issues, emerges as a fundamental tool to promote collective awareness. This study aimed to deliver environmental education lectures to analyze students’ level of knowledge and awareness regarding the general theme of waste. Two presentations were conducted for a total of 45 students, followed by a questionnaire at the end of each lecture. Notably, 90% of the students answered questions 05 and 06 correctly, while 100% answered question 07 correctly. It was observed that 80% of the students answered questions 08 correctly, 90% answered question 09 correctly, and 100% answered question 10 correctly. Additionally, 90% answered questions 11 and 13 correctly. Although 40% of the students demonstrated knowledge about reusing waste in the cultivation of plant species, only 60% admitted to having engaged in any waste reuse practices. In conclusion, the students exhibit a high level of knowledge and awareness regarding topics associated with solid waste. Furthermore, the effectiveness of environmental education was evident as a valuable tool in disseminating knowledge on the subject and assessing environmental consciousness within the academic community.